2005
DOI: 10.1530/rep.1.00641
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in men with Klinefelter syndrome

Abstract: Klinefelter syndrome (KS: 47,XXY), occurs in one in 1000 male births. Men with KS are infertile and have higher rates of aneuploidies in sperm compared with normal fertile men. In the course of analyzing recombination in a population of infertile men, we observed that four men in our study presented with KS. We examined whether these men differed in recombination parameters among themselves and relative to normal men. Even though the number of men with KS analyzed was small, we observed remarkable variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…KFS patients are often classified as having azoospermia, but there are reports stating that some KFS patients can produce normal sperm (Gonsalves et al, 2005). In contrast, some patients may have no sperm in the semen, but a few sperm exit in the testis (Lanfranco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…KFS patients are often classified as having azoospermia, but there are reports stating that some KFS patients can produce normal sperm (Gonsalves et al, 2005). In contrast, some patients may have no sperm in the semen, but a few sperm exit in the testis (Lanfranco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches on the ability of 47,XXY testes to yield postmeiotic cells exist. According to some researchers, 47,XXY spermatogonia have the potential to complete meiosis, resulting in both the increase in sex chromosomal aneuploidy rates as well as the presence of normal (haploid) spermatozoa [6,7,19,21,23]. According to others, primary 47,XXY spermatocytes are unlikely to complete meiosis, and spermatozoa of KS men arise from the patches of 46,XY spermatogonial stem cells in the testes that are affected by a compromised testicular environment and produce a high rate of aneuploid sperm due to meiotic errors.…”
Section: Discussionmentioning
confidence: 99%
“…They were reinforced by Egozcue et al [35] who identified the absence of 46,XY spermatogonia in patients negative for spermatids and spermatozoa, and by Mroz et al [36] who showed a clear absence of meiotic competence of 47,XXY cells in mice. Small quantities of studied germ cells such as 20-100 spermatogonia and primary spermatocytes in very few biopsies [1][2][3][4][5]8], as well as technical shortcomings, preclude a definite conclusion [1,4,17,19,20,23] (the study by Yamamoto et al [23] (2002) included 12 biopsies, but lacked information regarding the number of meiotic cells). The CCSS technique, which is based on corresponding size and morphology of the cells and their FISH images, enabled an extended study at three levels:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, immunocytogenetics can be combined with FISH to analyze recombination rates and crossover placement in individual chromosomes. While this assay also requires testicular biopsies to obtain material, pachytene has a long duration and nuclei are not as condensed as in diakinesis (Gonsalves et al, 2004(Gonsalves et al, , 2005Judis et al, 2004;Lynn et al, 2002;Ma et al, 2006;Sun et al, 2004aSun et al, , 2004bSun et al, , 2006Sun et al, , 2007Sun et al, , 2008aSun et al, , 2008b.…”
Section: Methods For Studying Critical Events Of Meiosismentioning
confidence: 99%